Pengaruh Maturitas Sistem Pengendalian Intern Pemerintah dan Kapabilitas Aparat Pengawasan Intern Pemerintah terhadap Indeks Persepsi Korupsi Indonesia - Suhartono, Raden (MASINTAN ACCOUNTANCY RESEARCH, 2026)
Research aims: This thesis aims to determine whether the maturity of the implementation of the government internal system (SPIP) and the capability of the provincial/district/city government internal control apparatus (APIP) in Indonesia affect the corruption perception index in Indonesia. Design/Methodology/Approach: The research was conducted with a quantitative approach processed with the help of SPPS use sample 508 districts/cities in Indonesia. Analysis which include descriptive, classical assumptions, simple linear regression, hypothesis testing t test, F test, and the coefficient of determination (R2). Research findings: The results of this study indicate that the maturity SPIP and the capabilities APIP in provinces/ districts/cities in Indonesia have an influence on the corruption perception index in Indonesia Theoretical contribution/Originality: This study is expected to serve as a reference for future researchers who wish to examine the influence of SPIP Maturity and APIP Capability on the Corruption Perception Index. Practitioner/Policy implication: Both the central and regional governments support increasing SPIP maturity and APIP capabilities to improve the Corruption Perception Index and eradicate corruption in Indonesia.